Investigation and response for farming-related stress among male farmers and their families - Sunderman, Aaren Michelle (Kansas State University, 2019)
Farming is one of the most stressful occupations due to its unpredictable nature, physical demands, management complexities and connection to global markets. There are several factors that are outside of the farmer’s control including the economy, weather, and machinery breakdowns. The significant increase in depression and suicide among male farmers is a cause for national concern. The 2019 Farm Bill has developed a Farm and Ranch Assistance Network (FRSAN) Competitive Grants Program intended to address farm and ranching-related stress and associated behavioral health issues by providing farmers with increased regional and state resources for support during times of need. However, high levels of stress, mid-west “boot strap” culture, stigma and customary masculine identity can prevent male farmers from seeking resources to increase their coping skills. Although customary resources of help, such as telephone helplines and mental health treatment are considered to be important helping resources, they have been shown to be ineffective since farmers do not typically access them. In this report, the author explores the economic, social and family-related issues confronting mid-west male farmers, and in response recommends a social marketing campaign to: a) improve the awareness of farmers and their families of the need for increased coping skills during tough farming-related times and b) motivates the male farmer to view the act of seeking help as an act of courage instead of an act of personal weakness. Though a social marketing campaign provides an essential step towards connecting farmers to external support, the limitations of a social marketing campaign are discussed.
Keywords: Male farmers; Farm stress; Farm families; Social marketing